A major genome region underlying artemisinin resistance in malaria. - Cheeseman, I; Miller, B; Nair, S; Nkhoma, S; Tan, A; Tan, J; Al Saai, S; Phyo, A; Moo, C; Lwin, K; Mcgready, R; Ashley, E; et al. (2012)
Evolving resistance to artemisinin-based compounds threatens to derail attempts to control malaria. Resistance has been confirmed in western Cambodia and has recently emerged in western Thailand, but is absent from neighboring Laos. Artemisinin resistance results in reduced parasite clearance rates (CRs) after treatment. We used a two-phase strategy to identify genome region(s) underlying this ongoing selective event. Geographical differentiation and haplotype structure at 6969 polymorphic single-nucleotide polymorphisms (SNPs) in 91 parasites from Cambodia, Thailand, and Laos identified 33 genome regions under strong selection. We screened SNPs and microsatellites within these regions in 715 parasites from Thailand, identifying a selective sweep on chromosome 13 that shows strong association (P = 10(-6) to 10(-12)) with slow CRs, illustrating the efficacy of targeted association for identifying the genetic basis of adaptive traits.